Desenvolvimento de metodologias de análises em fluxo com detecção amperométrica de múltiplos pulsos - Santos, Wallans Torres Pio dos (2009)
In this work we investigated potentialities of the multiple pulse amperometric detection (MPA) coupled with flow system. Simple analytical methodologies were developed for the simultaneous determination of analytes of pharmaceutical or environmental interest using MPA coupled with flow injection analysis (FIA) and highperformance liquid chromatography (HPLC). The simultaneous determination of ascorbic acid (AA) and paracetamol (PC) by FIA with amperometric detection was carried out by applying four sequential potential pulses (which are repeated within regular intervals) in function of time. AA is directly detected at +0.40 V / 100ms and PC indirectly at 0.00V/100ms through the reduction of the oxidation product (N-acetyl-p-benzoquinoneimine) electrochemically generated in the prior potential pulse (+0.65 V/100ms). The fourth potential pulse (-0.05 V/300ms) is applied for regeneration (cleaning) of the working gold electrode. The same principle of detection was applied for the simultaneous detection of active principles such as dipyrone (DI) and paracetamol (PC) in pharmaceutical formulations. As described in the previous method, the compounds were detected simultaneously through the application of four sequential potentials pulses in function of time on a glassy carbon working electrode. Dipyrone (DI) is directly detected at +0.40 V/100ms and paracetamol (PC) indirectly at 0.00 V/200ms. The oxidation product electrochemically generated from DI is also electroactive in the potential pulse applied for the indirect detection of PC (0.00 V). The selectivity for the PC detection in this potential pulse was obtained in function of the time of pulse application (200ms). Both simultaneous analyses were carried out under 0.10 mol L-1 acetate buffer (pH 4.7). The linear regressions obtained from analytical curves for simultaneous analyses presented excellent correlation coefficients (R = 0.999), as well as the recovery values (100 %). The analytical frequency for the proposed methodologies were calculated as 45 and 60 injections per hour for the analysis of DI/PC and AA/PC, respectively. The relative standard deviation for studies of repeatability of signal was lower than 1% for all analyses. The proposed method was used successfully for the determination of such compounds in pharmaceutical formulations. MPA detection coupled with FIA was also employed for PC quantification in the presence of high concentrations of AA using the standard addition method. In this case, it is possible to detect PC at trace level (LD = 0.20 mg L-1) in the presence of AA in 800-fold excess. (176.0 mg L-1). The present work also describes the possibility of coupling MPA detection with highperformance liquid chromatography (HPLC) through an electrochemical wall-jet cell. The MPA detection mode coupled with HPLC presents advantages such as fast response, high stability, and elevated selectivity of analytical response. The proposed electrochemical cell does not present either effects of peak broadening or carryover effects which make possible the monitoring of analytes separated by the chromatographic column with resolution comparable with a commercial UV detector. Moreover, this work demonstrates the versatility of the electrochemical cell developed in our laboratory for adaptation of commercial or home-made working electrodes for electrochemical detection in HPLC systems.